ANALYSIS OF DRUG UTILIZATION PATTERN IN CHRONIC KIDNEY DISEASE PATIENTS IN A TERTIARY CARE HOSPITAL, SOUTH INDIA - SIYAMALA DEVI T; HEMALATHA K; RENUKA A (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to assess the drug utilization pattern of various drugs prescribed in chronic kidney disease (CKD) patients in a tertiary care hospital. Methods: As a cross-sectional study 200 prescriptions were randomly selected from both the nephrology outpatient department and the inpatient ward. Patient demographics details, CKD staging, classes of drugs prescribed, and number of drugs prescribed were noted and data were analyzed with the World Health Organization core prescribing indicators. Results: Incidence of CKD is more common in the age group of 40–50 years (45%) with male predominance (70%). Hypertension, diabetes, and anemia are the common comorbid conditions seen with CKD. Anti-hypertensives, anti-anemic drugs, calcium supplements, and anti-diabetic drugs are the commonly prescribed drugs in CKD. Number of prescription contains that generic names are near optimal and drugs from the National List of Essential Medicine are optimal. Majority of the prescriptions contain on average 5 drugs. Conclusion: Diabetes and high blood pressure are the two most common causes of CKD with male dominance. Since polypharmacy is common in CKD patients , they should be monitored for drug – drug interaction and adverse drug reactions.